The Advocacy Journal Club: A Novel Method to Teach Pathologists About Health Policy. Issue 2 (11th October 2019) - Talmon, Geoffrey; Wolf, Alejandro; Molani, Mariam; Martin, Kimberly; Waibel, Elizabeth; Jacobs, Jeff; Wisecarver, James
Abstract: Objectives: To describe a method of educating pathologists about health policy. Methods: The Advocacy Journal Club was a series of six conferences. Topics were of those in the news or affecting local practice. Participants reviewed preparatory readings, completed a six- to 10-question pretest, attended an interactive presentation stressing advocacy groups' efforts, and completed a posttest. All were invited to complete a survey after the sessions. Results: Faculty and residents had increased posttest scores following each presentation with a significant difference in four and three sessions, respectively. More than 80% agreed they could discuss the topics with others and understood how regulations affect practice. More than 90% agreed that they gained an understanding of how involvement in organizations' advocacy initiatives affects policy. Conclusions: We present a method for educating pathologists about policy and the role of professional societies that could be implemented by nearly all graduate medical education programs.